Linear scaling relationships and volcano plots in homogeneous catalysis – revisiting the Suzuki reaction. Issue 12 (15th September 2015) - Busch, Michael; Wodrich, Matthew D.; Corminboeuf, Clémence
Abstract : Volcano plots, commonly used to identify attractive heterogeneous catalysts are applied, for the first time, to a prototypical homogeneous system. Abstract : Linear free energy scaling relationships and volcano plots are common tools used to identify potential heterogeneous catalysts for myriad applications. Despite the striking simplicity and predictive power of volcano plots, they remain unknown in homogeneous catalysis. Here, we construct volcano plots to analyze a prototypical reaction from homogeneous catalysis, the Suzuki cross-coupling of olefins. Volcano plots succeed both in discriminating amongst different catalysts and reproducing experimentally known trends, which serves as validation of the model for this proof-of-principle example. These findings indicate that the combination of linear scaling relationships and volcano plots could serve as a valuable methodology for identifying homogeneous catalysts possessing a desired activity through a priori computational screening.